Integrating Human Factors and Safety Management Frameworks in Maritime Occupational Accidents: Evidence from Indonesia (2003–2019) - Maharani, Mutia; Mustofa, Ahmad (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2025)
Abstract Maritime occupational safety remains a critical issue for Indonesia as an archipelagic nation heavily dependent on sea transportation. This study investigates the causal patterns of maritime occupational accidents in Indonesian waters from 2003 to 2019 by integrating official accident reports from the National Transportation Safety Committee (KNKT) and scholarly literature. A systematic analysis was conducted using the Human Factors Analysis and Classification System (HFACS-Maritime) and the International Safety Management (ISM) Code frameworks to identify human, technical, environmental, and organizational factors contributing to shipboard accidents. A total of 120 documented maritime accidents were analyzed, comprising incidents of fires, sinkings, groundings, collisions, and mechanical failures, which collectively resulted in 513 fatalities, 726 injuries, and 701 missing persons. The findings reveal that human error accounted for approximately 72% of all cases, followed by technical malfunctions (14%), adverse weather (8%), organizational deficiencies (4%), and cargo overloading (2%). The thematic analysis based on HFACS highlighted four dominant error dimensions: unsafe acts, preconditions for unsafe acts, unsafe supervision, and organizational influences. These results demonstrate that systemic issues—such as fatigue, inadequate training, poor supervision, and weak safety culture—remain major underlying causes of accidents, despite Indonesia’s adoption of the SOLAS Convention and ISM Code. The study concludes that improving maritime occupational safety requires a paradigm shift from regulatory compliance toward proactive risk management and cultural transformation. Policy recommendations include enhancing institutional oversight, implementing competency-based crew training, adopting fatigue management systems, and strengthening enforcement of ISM Code compliance. The integration of HFACS and ISM Code frameworks provides a holistic understanding of maritime safety, offering a foundation for evidence-based policymaking to build a more resilient and safety-oriented Indonesian maritime sector.